The Gospel of Matthew in its historical and theological context: papers from the International Conference in Moscow, September 24 to 28, 2018 - Seleznëv, Michail; Loader, William R. G.; Niebuhr, Karl-Wilhelm (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Der Band enthält Beiträge einer internationalen Konferenz zum Matthäusevangelium in Moskau 2018. Aufsätze von orthodoxen, katholischen, protestantischen und anglikanischen Bibelwissenschaftlern behandeln historische Kontexte, theologische Themen und Aspekte der Wirkungsgeschichte des ersten Evangeliums.InhaltsübersichtPart One: Matthew in Reception and Research Metropolitan Hilarion Alfeyev: The Gospel of Matthew in Church Tradition and Modern Scholarship – Tobias Nicklas: From Gospel Book to Virtual Reality: A Neglected Aspect of the Gospel of Matthew's Ancient Reception History – Ian Boxall: Joseph Son of David in the Reception History of Matthew's Gospel – Richard Burridge: Matthew and Gospel Genre: A Critical Review of the Last 25 Years, 1993–2018 – Thomas R. Hatina: Scripture, Memory, and Time: Matthew's Fulfilment Quotations as Historiographical Devices Part Two: Matthew in Context Carl R. Holladay: The Gospel of Matthew Within the Context of Second Temple Judaism – Michael Tilly: Matthew and Jewish Apocalypticism – R. Alan Culpepper: The Place of Matthew in Early Christianity – William R. G. Loader: Matthew and John: Two Different Responses to a Similar Situation Part Three: Themes and Motifs in Matthew Jan Joosten: The Text of Old Testament Quotations in Matthew – Joel Marcus: John the Baptist in the Gospel of Matthew: Comparison and Distinction – Craig S. Keener: An Epitome of Matthean Themes: Matthew 28:18–20 – Paul Foster: The Depiction of God in the Gospel of Matthew – Matthias Konradt: Following Jesus and Fulfilling the Law: Considerations on the Ethical Conception of the Gospel of Matthew – Roland Deines: Jesus and the Torah according to the Gospel of Matthew – Karl-Wilhelm Niebuhr: Matthew's Idea of being Human: God's Righteousness and Human Responsibility according to the Gospel of Matthew – Christian Blumenthal: Basileia is Gaining Space: God's Will, Mimesis of Christ and the Spatial Shaping of the Basileia in Matthew's Gospel – Alexey Somov: Resurrection of the Righteous Sufferers in the New Testament: The Case of Matthew 27:52–53